Improved Detection of Anterior Circulation Occlusions: The “Delayed Vessel Sign” on Multiphase CT Angiography - Byrne, D.; Sugrue, G.; Stanley, E.; Walsh, J.P.; Murphy, S.; Kavanagh, E.C.; MacMahon, P.J. (American Journal of Neuroradiology, 2017)
BACKGROUND AND PURPOSE: Multiphase CTA, a technique to dynamically assess the vasculature in acute ischemic stroke, was primarily developed to evaluate collateral filling. We have observed that it is also useful in identifying distal anterior circulation occlusions due to delayed anterior circulation opacification on multiphase CTA, an observation we term the “delayed vessel sign.” We aimed to determine the usefulness of this sign by comparing multiphase CTA with single-phase CTA.MATERIALS AND METHODS: All 23 distal anterior circulation occlusions during a 2-year period were included. Ten M1-segment occlusions and 10 cases without a vessel occlusion were also included. All patients had follow-up imaging confirming the diagnosis. Initially, the noncontrast CT and first phase of the multiphase CTA study for each patient were blindly evaluated (2 neuroradiologists, 2 radiology trainees) for an anterior circulation occlusion. Readers' confidence, speed, and sensitivity of detection were recorded. Readers were then educated on the “delayed vessel sign,” and each multiphase CTA study was re-examined for a vessel occlusion after at least 14 days.RESULTS: There was significant improvement in the sensitivity of detection of distal anterior circulation vessel occlusions (P < .001), overall confidence (P < .001), and time taken to interpret (P < .001) with multiphase CTA compared with single-phase CTA. Readers preferred MIP images compared with source images in >90% of cases.CONCLUSIONS: The delayed vessel sign is a reliable indicator of anterior circulation vessel occlusion, particularly in cases involving distal branches. Assessment of the later phases of multiphase CTA for the delayed vessel sign leads to a significant improvement in the speed and confidence of interpretation, compared with single-phase CTA.MPCTAmultiphase CTASPCTAsingle-phase CTA